2019
DOI: 10.1177/1359105319886049
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms are related to boredom proneness in patients receiving hospital care, regardless of alcohol status, lifestyle, or social support

Abstract: We examined the relationship between boredom proneness and psychological distress in patients receiving hospital care due either to excessive alcohol consumption or to gastrointestinal diseases. Sociodemographic data were collected together with boredom proneness subscales (internal/external lack of stimulation), psychological distress, physical activity, and social support. Boredom proneness due to a lack of external stimulation seemed to constitute a prominent personality trait in patients with alcohol consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Thus, it can be concluded that psychological distress, BP, and FoMO are all influencing factors for IA ( Chou et al, 2018 ; Elhai, Gallinari, et al, 2020 ; Elhai, Yang, et al, 2020 ). Individuals with high levels of psychological distress are more likely to report higher levels of FoMO ( Elhai, Yang, et al, 2020 ), have more BP ( Constant et al, 2019 ), and are more vulnerable to problematic Internet use ( Elhai, Vasquez, et al, 2018 ). The present study found that during the COVID-19 pandemic, the reporting rate of young people's IA was 28.1% higher than a survey on adolescent IA (7.7%) before COVID-19 outbreak in China ( Shen et al, 2020 ) and the rate of IA (6.03%) during the spread of COVID-19 in China ( Duan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be concluded that psychological distress, BP, and FoMO are all influencing factors for IA ( Chou et al, 2018 ; Elhai, Gallinari, et al, 2020 ; Elhai, Yang, et al, 2020 ). Individuals with high levels of psychological distress are more likely to report higher levels of FoMO ( Elhai, Yang, et al, 2020 ), have more BP ( Constant et al, 2019 ), and are more vulnerable to problematic Internet use ( Elhai, Vasquez, et al, 2018 ). The present study found that during the COVID-19 pandemic, the reporting rate of young people's IA was 28.1% higher than a survey on adolescent IA (7.7%) before COVID-19 outbreak in China ( Shen et al, 2020 ) and the rate of IA (6.03%) during the spread of COVID-19 in China ( Duan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the lack of mental stimulation could constitute a significant vulnerability factor for excessive eating [ 112 ] and drinking [ 113 ]. Som et al found a higher proportion of food addiction in unemployed patients [ 66 ], and our previous work showed a greater predisposition to boredom in patients with excessive drinking [ 113 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the lack of mental stimulation could constitute a significant vulnerability factor for excessive eating [ 112 ] and drinking [ 113 ]. Som et al found a higher proportion of food addiction in unemployed patients [ 66 ], and our previous work showed a greater predisposition to boredom in patients with excessive drinking [ 113 ]. One possible explanation is that some vulnerable people use these compulsive behaviors to cope with excessive lack of internal and/or external stimulation in their daily lives, which may increase the risk of addiction and jeopardize their social and professional functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Our participants were representative of patients hospitalized for alcohol issues, whose characteristics have been investigated (Constant et al, 2015;Constant et al, 2017;Constant et al, 2019). They reported mental and physical functioning below average, since alcohol dependence includes the impairment of functional status, activity limitations, and restrictions in social interactions (Levola et al, 2014;Vancampfort et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…But overall, they reported low levels of alcohol urges and psychological distress, although these symptoms tend to be more prevalent in people with alcohol dependence (Constant et al, 2015), and 4 in 10 were sober for more than a week before admission to the 7-day detoxification program. This probably reflects the particular situation of patients in detoxification programs, where mental health and withdrawal symptoms are carefully monitored and managed (Constant et al, 2019;Giorgi et al, 2015;Sander and Jux, 2006). Baseline assessments were indeed conducted at the beginning of the 7-day hospital stay precluding patients' exposure to drinking cues, stressful events and negative emotions.…”
Section: Discussionmentioning
confidence: 99%